Social development: San Mateo de Otao and Callahuanca, 2017 - Díaz Encinas, Alida Isidora (2019)
When analyzing the evolution of development and social changes in the population of the districts of San Mateo de Otao and Callahuanca - Huarochirí 2017, we find a series of transformations, mainly in agriculture, originally from sustenance, to agriculture oriented towards marketing, for the internal and external market. This despite the shortage of water for irrigation, the abandonment of villages and annexes that are above 3,000 meters above sea level and the migration of the young population, detracting from the local workforce. We also verify the lack of attention to cultural heritage and education, in terms of health, primary care prevails. Finally, to encourage the process of development and changes in the social components of San Mateo de Otao and Callahuanca, it is necessary to implement spatial equity policies and socio-economic actions for all peoples and annexes, with adequate local government management in the use of land and farming.